2006
DOI: 10.1111/j.1600-0854.2006.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Causes Centrosomal Defects Resulting in Chromosomal Segregation Abnormalities

Abstract: Chlamydiae traffic along microtubules to the microtubule organizing center (MTOC) to establish an intracellular niche within the host cell. Trafficking to the MTOC is dynein dependent although the activating and cargolinking function of the dynactin complex is supplanted by unknown chlamydial protein(s). We demonstrate that once localized to the MTOC, the chlamydial inclusion maintains a tight association with cellular centrosomes. This association is sustained through mitosis and leads to a significant increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 47 publications
(63 reference statements)
8
101
0
1
Order By: Relevance
“…Adducin coimmunoprecipitates with components of this complex, such as p150 Glued , Arp1 and dynamitin (Holleran et al, 1998). Grieshaber et al (2003) recently demonstrated that, while chlamydial inclusions traverse intracellularly via dynein-mediated microtubular interactions, chlamydial migration is unaffected by disruption of the dynactin complex. The localization of a-adducin in close proximity to the chlamydial inclusion membrane may provide clues to novel interactions between components of the dynactin complex and the developing chlamydial inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adducin coimmunoprecipitates with components of this complex, such as p150 Glued , Arp1 and dynamitin (Holleran et al, 1998). Grieshaber et al (2003) recently demonstrated that, while chlamydial inclusions traverse intracellularly via dynein-mediated microtubular interactions, chlamydial migration is unaffected by disruption of the dynactin complex. The localization of a-adducin in close proximity to the chlamydial inclusion membrane may provide clues to novel interactions between components of the dynactin complex and the developing chlamydial inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…While the chlamydiae are known to affect many host cellular processes, including apoptosis (Miyairi & Byrne, 2006), vesicular morphogenesis (Beatty, 2006;Carabeo et al, 2003;Grieshaber et al, 2003;Rzomp et al, 2003;Scidmore & Hackstadt, 2001;Scidmore et al, 1996aScidmore et al, , b, 2003, cytokinesis (Greene & Zhong, 2003), lipid metabolism (Hackstadt et al, 1995), and host-cell immune responses (Lad et al, 2005), many aspects of intracellular hostpathogen interactions remain unclear. Chlamydial proteins that are involved in such alterations include proteins secreted into the host cytosol and those localized to the inclusion membrane (Rockey & Rosquist, 1994;Zhong et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Soon after entry, nascent inclusions are transported along microtubules to the microtubule organizing center (MTOC) in a dynein-dependent but dynactin-independent manner (Clausen et al 1997;Grieshaber et al 2003;Grieshaber et al 2006), suggesting that one or more unknown bacterial effectors mimic the cargobinding activity of dynactin and tether the inclusion to dynein and/or to centrosomes. Src family kinases are required in human-adapted Chlamydia strains for inclusions to migrate to the MTOC and for intracellular growth, even though they are dispensable for binding and entry (Mital and Hackstadt 2011).…”
Section: Transport To the Peri-golgi Regionmentioning
confidence: 99%
“…One or more of these Incs may recruit active Src family kinases to the inclusion to promote microtubule nucleation, dynein-dependent movement, and sphingomyelin acquisition (Mital et al 2010;Mital and Hackstadt 2011). The inclusion maintains a dynein-dependent association with the centrosome throughout the cell cycle, resulting in supernumerary centrosomes, abnormal spindle poles, and segregation defects (Grieshaber et al 2006;Johnson et al 2009). These findings are intriguing in light of the association of Chlamydia and human papilloma virus-associated cervical cancer (Wallin et al 2002).…”
Section: Transport To the Peri-golgi Regionmentioning
confidence: 99%
“…12 Chlamydia trachomatis was epidemiologically linked to increased risk of developing cervical cancer. 13 It affects genome stability by several mechanisms: multipolar spindle formation, 14,15 spindle assembly checkpoint override, 16 cytokinesis failure, 17,18 and induction of DNA damage coupled to impaired repair mechanisms. 19 The interplay between Lm and the host cell cycle is understudied.…”
Section: Introductionmentioning
confidence: 99%